The role of the religious factor in political processes in Israel - A. V. Krylov (Международная аналитика)
This article studies the influence of religion on political and social processes in Israel. Modern Israel is a complicated multi-ethnic and multi-religious society. Israel is home to over 8 million people and approximately a quarter of its citizens are non-Jews (Muslim Arabs and Christian Arabs, Druze, Bedouins, Circassians and etc.). In spite of the fact that the Israeli system of law provides “the complete equality of social and political rights to all its inhabitants irrespective of religion, race or sex”, many Arabs and other non-Jews citizens of the State are not really integrated into Israeli society and do not feel themselves full citizens of the State that seeks to position itself exclusively as a «Jewish State».In addition the tension between Israel’s Middle Eastern and European identities is personified in the contradictions between Ashkenazim and Sephardim. There are also religious differences between Jews who identify themselves with the ultra-Orthodox, religious nationalists (so called “Hardelim” - an acronym of two words in Hebrew – “Hared” (ultra-orthodox) and “Leumi” (nationalist)), traditionalists and secular Jews. The article notes that the current «Likud» government supported by the religious parties actually strengthens the tendency to clericalization of Israeli political and social life.The author also makes an attempt to understand and analyze the basic historical, philosophical and religious aspects of the National-Religious trend in Israeli politics. This trend turned into a powerful force after a Jewish religious fanatic Yigal Amir had killed Prime Minister Yitzhak Rabin in 1995.The research reveals the forms and methods, aims and objectives of the Israeli official settlement policy, determines the attitude of the religious parties and groups towards the settlement movement and indicates a negative influence of the settlement factor on the Israeli-Palestinian negotiating process and political situation in the Middle East as well.